Cytonuclear discordance among Southeast Asian black rats (Rattus rattus complex). Issue 4 (24th December 2012) - Pagès, Marie; Bazin, Eric; Galan, Maxime; Chaval, Yannick; Claude, Julien; herbreteau, Vincent; Michaux, Johan; Piry, Sylvain; Morand, Serge; Cosson, Jean‐François
Abstract Black rats are major invasive vertebrate pests with severe ecological, economic and health impacts. Remarkably, their evolutionary history has received little attention, and there is no firm agreement on how many species should be recognized within the black rat complex. This species complex is native to India and Southeast Asia. According to current taxonomic classification, there are three taxa living in sympatry in several parts of Thailand, Cambodia and Lao People's Democratic Republic, where this study was conducted: two accepted species (Rattus tanezumi, Rattus sakeratensis) and an additional mitochondrial lineage of unclear taxonomic status referred to here as 'Rattus R3'. We used extensive sampling, morphological data and diverse genetic markers differing in rates of evolution and parental inheritance (two mitochondrial DNA genes, one nuclear gene and eight microsatellite loci) to assess the reproductive isolation of these three taxa. Two close Asian relatives, Rattus argentiventer and Rattus exulans, were also included in the genetic analyses. Genetic analyses revealed discordance between the mitochondrial and nuclear data. Mitochondrial phylogeny studies identified three reciprocally monophyletic clades in the black rat complex. However, studies of the phylogeny of the nuclear exon interphotoreceptor retinoid‐binding protein gene and clustering and assignation analyses with eight microsatellites failed to separate R. tanezumi and R3. Morphometric analyses were consistent with nuclear data. The incongruence between mitochondrial and nuclear (and morphological) data rendered R. tanezumi/R3 paraphyletic for mitochondrial lineages with respect to R. sakeratensis. Various evolutionary processes, such as shared ancestral polymorphism and incomplete lineage sorting or hybridization with massive mitochondrial introgression between species, may account for this unusual genetic pattern in mammals.